Gamifying the university classroom: a comparative analysis of game dimensions through educational Escape Room and a digital board game - Mauri-Medrano, Marta; González-Yubero, Sara; Falcón-Linares, Carolina; Cardoso-Moreno, María Jesús (Frontiers in Education, 2024)
Introduction University education is looking for innovative ways to enrich the teaching-learning process. Methods This study aims to describe and compare two gamified experiences: an educational Escape Room and a digital goose board game with Genially. The design of this research follows a quantitative correlational methodology. A total of 135 university students in the first year of the Bachelor’s Degree in Primary Education participated in the study. Results Data were collected using the Gamified Game Experience Scale (GAMEX). The results of contrasting means for the game dimensions between both gamified experiences reveal a significant variability (p < 0.01) in favor of the Escape Room in fun, absorption, creative thinking, activation and mastery. On the other hand, the absence of negative affect was significant (p < 0.05) in favor of the digital board game. Discussion It could be said that the educational Escape Room manifests itself as a powerful resource for learning. However, it can induce a high level of stress, generating discomfort, hostility and frustration in students, so its implementation is not free of negative effects. These findings provide additional empirical evidence that could guide the design of gamified experiences in the Higher Education environment.